Hidrocistoma écrino e apócrino na pálpebra - Casuística na Faculdade de Medicina de Botucatu- São Paulo - Schellini, Silvana Artioli [UNESP]; Da Costa Pinto, A. P. [UNESP]; De Castilho, C. N. [UNESP]; Achilles, A. B. [UNESP]; Padovani, Carlos Roberto [UNESP]; Marques, Mariângela Esther Alencar [UNESP] (My University, 2001)
Background - Hidrocystomas ecrine and apocrine may be observed in the eyelids. Objective - The purpose of this study was to observe the occurrence of eyelid hidrocystoma (eccrine or apocrine), as well as the relation between clinical and histopathological diagnosis. Patients and Methods - 42 patients were selected, with a total of 52 lesions, attended between January 1990 to April 1999, at the Botucatu Medical School, with diagnosis of hidrocystoma confirmed by histopathology diagnosis. Result - Hidrocystoma occurred in 0.07% of patients undergoing lesion removal during this period. Eccrine and the apocrine hidrocystoma were frequently observed in female patients, aged over 40 years. The clinical picture ranged from about 1 to 5 years. The lesions were mainly located in the lower eyelid and presented as a single lesion. The clinical diagnosis agreed with the histopathological diagnosis in 67.31% of the apocrine hidrocystomas, and 9.62% of the eccrine hidrocystomas. Conclusions - Apocrine hidrocystoma was the most frequently observed eyelid hidrocystoma. The correlation between clinical and histopathological diagnosis was higher for apocrine hidrocystomas.
Eyelid eccrine and apocrine hidrocystoma - Occurrence at the Faculdade de Medicina de Botucatu - São Paulo
Keywords: Apoccrine hidrocystoma; Benign eyelid lesion; Eccrine hidrocystoma; Moll's cyst; adult; apocrine gland; benign tumor; blue nevus; Brazil; clinical article; eyelid tumor; female; hidradenoma; histopathology; human; male; meibomian gland; sweat gland disease